Cochlear nerve dysplasia in unilateral severe to profound congenital sensorineural hearing loss – Prevalence in Australian children and the impact of socioeconomic disadvantage on its management. (February 2023) - Ryan, P.; Huins, C.T.; O'Brien, K.J.; Misra, S.; Birman, C.S.
Abstract: Introduction: Congenital unilateral sensorineural hearing loss (cuSNHL) carries potentially significant social, educational, and developmental consequences. Early diagnosis enables investigation, and consideration of options for management and early intervention, helping to mitigate the effects of hearing loss. Cochlear nerve dysplasia (CND) is a prominent cause of cuSNHL and may affect candidacy for cochlear implantation. Socioeconomic disadvantage may impact on a patient's family's capacity to participate in necessary intervention and follow-up. Methods: Infants with severe-profound cuSNHL referred to a large Australian quaternary pediatric center between October 2004 and December 2020 were retrospectively included. Audiometric and clinical data, and the presence of hearing loss risk factors were obtained from a prospectively collated database. In Australia MRI scans are provided free-of-charge to citizens and residents. MRI scans were reviewed to determine the status of the nerves within the internal acoustic meatus (IAM grade) along with attendance rates. Travel distance to the hospital was also calculated. Reasons for non-attendance at MRI were obtained from patient medical records and correspondence. Socioeconomic, educational, and occupational indices, and travel distances were obtained using patient residential postcodes with reference to Australian Bureau of Statistics data. Results: A total of 98 patients were reviewed, 64.3% ( n = 63) of whom underwent MRI. The median age at diagnosis was 40 days (IQR 27). The prevalence of CND was 75% ( n = 47). Importantly, there was no significant difference in the degree of hearing loss between IAM grades ( F (4, 57) = 1.029, p = 0.405). Socioeconomic indices were significantly lower in patients not attending MRI investigations compared with patients who did attend. Travel distance was not significantly different between the two groups. Conclusion: CND is a prominent cause of cuSNHL in Australian infants. MRI at a young age allows parent education regarding management options and timely intervention where indicated. Socioeconomic disadvantage significantly impacts on participation in further routine assessment of cuSNHL, potentially limiting management options for these children long term. Highlights: Cochlear nerve dysplasia is a common cause of unilateral sensorineural hearing loss. Radiographic absence of cochlear nerves does not imply physiologic absence. Patients from lower socioeconomic groups are less likely to engage in medical care.